PENGARUH KINERJA KEUANGAN, KINERJA LINGKUNGAN, SIZE, DANUKURAN DEWAN KOMISARIS TERHADAP CSRDISCLOSURE - Amelia Amelia; Ari Dewi Cahyati (JRAK: Journal of Accounting Research and Computerized Accounting, 2015)
The purpose of this study was to determine the effect of financial performance, environmentalperformance, size and board size on the disclosure of Corporate Social Responsibility (CSR Disclosure) in miningcompanies listed on the Stock Exchange during 2010-2014. The method used is descriptive with quantitativeapproach.. Data of this research is secondary data, using the financial statements of mining companies listed in theStock Exchange gained through www.idx.co.id for the year. 2010-2014 Samples were selected using purposivesampling method. The analysis technique used in this research is multiple linear regression analysis.The resultsshowed that the variables of financial performance, as measured by ROA and DER, and company size has nosignificant effect on the disclosure of corporate social responsibility, while variable environmental performance andboard size have a significant effect on the disclosure of corporate social responsibility